Socio-environmental projections of lithium exploitation in Puno: configuration of the social territory by the lithiferous activity in Peru by 2024 (Sustainability in Debate, 2025)
The study aims to identify key socio-environmental considerations for the strategic management of lithium in Peru, with a focus on the spatial configuration of the territory. This is a qualitative research study that observed concerns in some Puno communities about the impacts on their economic activities and daily lives, as well as about pollution and uneven benefits for the areas of influence. Direct interactions with the project owner, due to the state’s insufficient institutional capacity, were identified through interviews with its agents. By comparing this information with documentary and theoretical material, policy recommendations can be developed to focus on the specification of the regulatory framework, expansion of participation, and analysis of similar experiences.